Islamic Faith-Based Organizations and Poverty Reduction in Bangladesh: A Social Work Perception - Isahaque Ali; Azlinda Azman; Paramjit Singh Jamir Singh; Syazwani Drani; Mohammed Mamun Rashid (Social Work and Society)
The development studies have traditionally neglected the role of religious faith and its role in the lives of the poor throughout the developing world. However, recently, there has been greater recognition and value given to the contributions of Faith-Based Organizations (FBOs) in providing social services and poverty reduction. Bangladesh is a bulky and profoundly densely populated country in South Asia with an estimated 170 million population for the year 2018. The poverty rate is also the highest in rural areas, at 36%, compared with 28% in the urban area (BBS, 2016). Poor people unable to meet their basic needs due to unequal distribution of income, and that income gap is getting wider between the rich and the poor. Muslim FBOs are one of the largest sectors of development agencies that are making significant contributions towards historical poverty reduction process in Bangladesh. Zakat (almsgiving) and waqf (public charity) are Islamic faith-based organizations and is seen to be being underutilized for poverty reduction in many of these poor Muslim countries. Since zakat constitutes one of the pillars of Islam, it is logical to assume that policymakers should pay serious attention to it. This conceptual paper aims to examine the role of FBOs for poverty reduction in the light of Islam. The paper contends that the elements of social work practice can further contribute to the community development by allowing social work practitioners to engage in the analysing the existing policies or advocating for a relevant policy with regards to alleviate poverty in Bangladesh. It is also the role of the social workers to guide the relevant stakeholders involving in the poverty alleviation, either locally and globally, to implement further new outcomes related to poverty alleviation concerns.